Foundations of Object-Oriented Programming Using .NET 2.0 Patterns - Gross, Christian (Apress, 2012)
Patterns are an interesting topic that has already been thoroughly discussed. The book that originally started the pattern phenomenon was Design Patterns: Elements of Reusable Object- Oriented Software by Erich Gamma et al. (Boston: Addison-Wesley, 1995). At the time the book was published, it presented new ideas and concepts. Now it has become the reference book of design patterns, and the described design patterns have become the basis of all sorts of applications. This book is an explanation of design patterns as applied to the .NET 2.0 Framework. Some of the patterns are from Design Patterns: Elements of Reusable Object-Oriented Software, and others are from other sources. The focus of this book is not to explicitly define the patterns, but to illustrate the patterns in the context of using them with a programming language like C#, because the original design patterns were illustrated using C++, and there are major differences between that language and .NET and C#.